KELAYAKAN FINANSIAL PEREMAJAAN OPTIMAL TANAMAN KARET DI KEBUN NGOBO PT. PERKEBUNAN NUSANTARA IX JAWA TENGAH - Pratama, Wahid Cahya; Bayu, Bayu (Agros Journal of Agriculture Science, 2024)
Normatively, companies can determine the time for replanting of rubber plant at the age of the plant until the 27th year of maturity (TM), but in practice in the field many are replanting before the 27th year of TM or after the plant produces (20th TM). The aim of this research was to determine the optimal time and proportion of estate area for replanting of rubber plant and to analyze the response if there is a change in the selling price of rubber and a change in production costs. Sampling was carried out purposively, at Ngobo Estate research location of PT Perkebunan Nusantara IX in Semarang Regency area. The research results show: 1) The optimal time for replanting rubber plant in Ngobo Estate under normal conditions is the 31st year and the appropriate optimal area proportion is 3.23% of the rubber estate area owned company. 2) A 10% reduction in the selling price of rubber results in the optimal time 29th year for replanting and the same proportion of area 3,47%.. Meanwhile, a 20% reduction in the selling price of rubber results in the optimal time for rubber plant replanting in the 30th year. An increase in production costs starting from 10% results in the optimal time for replanting in the 31st year, different things happen for a 20% increase in costs resulting in the optimal time for rubber plant replanting being in the 30th year. Meanwhile, a 10% reduction in the selling price of rubber and a 20% increase in production costs results in the optimal time for replanting being 28th year. Keywords: optimum replanting, rubber plant, Ngobo estate INTISARISecara normatif, perusahaan dapat menentukan waktu peremajaan tanaman karet pada umur tanaman sampai tanaman menghasilkan (TM) tahun ke 27, namun dalam praktik di lapangan banyak yang diremajakan sebelum tanaman menghasilkan (TM) tahun ke 27 atau setelah tanaman menghasilkan (TM 20). Tujuan penelitian ini dilakukan untuk menentukan saat dan proporsi luasan kebun peremajaan optimal tanaman karet serta menganalisis responnya jika terjadi perubahan harga jual karet dan perubahan biaya produksi. Di lokasi penelitian Kebun Ngobo PT Perkebunan Nusantara IX di wilayah Kabupaten Semarang. Hasil penelitian menunjukkan: 1) Saat optimal peremajaan tanaman karet di Kebun Ngobo pada kondisi normal adalah tahun ke 31 dan proporsi luasan optimal yang tepat adalah 3,23% dari luasan kebun karet milik perusahaan. 2) Penurunan harga jual karet 10% menghasilkan saat optimal peremajaan ditahun ke 29 dengan proporsi luasan (3,47%). Sedangkan untuk penurunan harga jual karet 20% menghasilkan dan saat optimal peremajaan tanaman karet di tahun ke 30. Kenaikan biaya produksi mulai dari 10% menghasilkan saat optimal peremajaan di tahun ke 31, hal berbeda terjadi untuk kenaikan biaya 20% menghasilkan saat optimal peremajaan tanaman karet menjadi di tahun ke 30. Sementara penurunan harga jual karet 10% dan biaya produksi naik 20% menghasilkan saat optimal peremajaan tahun 28. Kata Kunci: Peremajaan ptimal, Tanaman Karet, Kebun Ngobo